2021
DOI: 10.30596/jimb.v22i1.5147
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kinerja Berbasis Manajemen Bakat, Servant Leadership Dan Komitmen Organisasi

Abstract: This study aims to analyze the effect of talent management and servant leadership on HR performance through organizational commitment. The population in this study were all employees of PSDA-ESDM Semarang. The sampling technique using purposive random sampling is a sampling technique that uses certain criteria or considerations. Samples taken were 84 respondents, with a research instrument in the form of a questionnaire. Data analysis uses multiple linear regression. The results showed that talent managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 6 publications
3
4
0
8
Order By: Relevance
“…The results of research by Kamanjaya et al, (2017) (2017) declare with higher servant leadership can form organizational commitment so as to have a positive impact on improving employee performance. The results of research by Hasanah & Mujanah (2020) , Ekhsan &Aziz (2021) , andNugroho &Putro (2021) also support the statement that higher organizational commitment will streng then the influence of servant. leadership in improving employee performance.…”
Section: Performancesupporting
confidence: 66%
See 3 more Smart Citations
“…The results of research by Kamanjaya et al, (2017) (2017) declare with higher servant leadership can form organizational commitment so as to have a positive impact on improving employee performance. The results of research by Hasanah & Mujanah (2020) , Ekhsan &Aziz (2021) , andNugroho &Putro (2021) also support the statement that higher organizational commitment will streng then the influence of servant. leadership in improving employee performance.…”
Section: Performancesupporting
confidence: 66%
“…These results can be concluded that the third hypothesis which states servant leadership has a positive and significant effect on employee performance and is acceptable. These results have been supported by the research results of Setyaningrum et al, (2017) , Aprilliansyah et al, (2018) , Hasanah & Mujanah (2020) , Ekhsan & Aziz (2021) , Nugroho & Putro (2021) and Pakpahan et al , (2021) who stated servant leadership has a positive and significant effect on employee performance. This result is different from Kamanjaya et al, ( 2017) and Sahem et al, ( 2020) which has positive but not significant research results on the relationship between servant leadership and employee performance.…”
Section: Description Respondentsupporting
confidence: 54%
See 2 more Smart Citations
“…This is in line with research conducted by Irawati, et al, (2017) which shows that the variables of talent management and human resource management have a positive and significant effect on employee performance. This research is also supported by Nugroho and Putro (2021), Diniati, et al, (2018), and Nina and Astuti (2016. What distinguishes this research is that the method is not quantitative but qualitative.…”
Section: ) Analysis Of the Role Of Good Corporate Governance And Tale...mentioning
confidence: 82%